2020
DOI: 10.1038/s41598-020-70913-2
|View full text |Cite
|
Sign up to set email alerts
|

LINC00641/miR-582-5p mediate oxaliplatin resistance by activating autophagy in gastric adenocarcinoma

Abstract: The poor prognosis of gastric adenocarcinoma is partly due to chemotherapy failure, especially the oxaliplatin-based chemotherapy. However, the specific mechanism of oxaliplatin resistance is unclear. We aim to find the roles that LINC00641 and miR-582-5p play in regulating oxaliplatin resistance. Quantitative reverse transcriptase-PCR was used to evaluate the expression of LINC00641 and microRNA-582-5p (miR-582-5p) in gastric cancer both in vivo and in vitro. Transwell and CCK-8 assays were performed; and LC3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 17 publications
(19 reference statements)
0
21
0
Order By: Relevance
“…The expression of LINC00641 was also found to be high in gastric cancer. It demonstrated that LINC00641 promoted cell migration and proliferation and mediated oxaliplatin resistance by activating autophagy [ 25 ]. Consisted with the results, LINC00641 was also increased in RCC and high LINC00641 expression was associated with TNM stage and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of LINC00641 was also found to be high in gastric cancer. It demonstrated that LINC00641 promoted cell migration and proliferation and mediated oxaliplatin resistance by activating autophagy [ 25 ]. Consisted with the results, LINC00641 was also increased in RCC and high LINC00641 expression was associated with TNM stage and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Linc00641 is involved in gastric tumorigenesis and progression. Linc00641 downregulation inhibits cell proliferation and migration in gastric adenocarcinoma [ 17 ]. High expression of linc00641 was observed in gastric cancer specimens and was correlated with patient prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…High expression of linc00641 was observed in gastric cancer specimens and was correlated with patient prognosis. Moreover, linc00641 mediated the chemoresistance of oxaliplatin via the induction of autophagy by sponging miR-582-5p in gastric cancer [ 17 ]. Furthermore, gastric cancer patients with oxaliplatin resistance have higher levels of linc00641 expression [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations